Mythical Cognition and Artistic Method - Kokbas, Zhazira; Aimukhambet, Zhanat; Kurmambayeva, Karlygash; Smagulova, Nurgul; Yesmatova, Mendykyz (International Journal of Criminology and Sociology, 2022)
The aim of the study is to research mythical cognition, which is of particular importance for deep understanding of the issue of mythologism, mythopoetics in literature, and world literary science. The leading research methods for this issue is the analysis method. The specifics of using the mythopoetic method in poetry was given by the poetry of Tynyshtykbek Abdikakimov, the artistic and aesthetic value of mythical knowledge was revealed. The article also analyses the differences between mythological and poetic cognition and proves the value and power of the mythopoetic method in fiction. The system of mythological thinking of a mythological worldview not only determines Kazakh national worldview, but also transfers the fruits of mythical consciousness to the visual system, forming a huge channel of artistic approach. The novelty of the study is determined by the fact that the actual problem of literary criticism was analysed, which is a spiritual value, the transformation of mythological consciousness into poetic consciousness in the poems of the poet, into the basis of images and poetic expressions formed in the system of modern literary thinking. The practical significance of the study is determined by the necessity to study the activity of mythical knowledge in poetics.